THE COST OF COLONOSCOPY – A WORLDWIDE VIEW. (8th June 2013) - Haslam, R; El-Khassawneh, S; Sucher, U
Abstract : Introduction: Allianz Worldwide Care is a private medical insurer, specialising in providing international (expatriate) health insurance for employees, individuals and their dependants, wherever they are in the world. Allianz Worldwide Care insure over 250, 000 people in more than 150 countries. As an international insurer, we see a wide price variation in different regions of the world, for the same procedure. Aims/Background: To assess the price differences for a colonoscopy +/− biopsies between different countries in the world. We aim also to highlight the differences in length of stay for this procedure around the world. Method: We assessed all pre-authorisation Guarantees for full colonoscopy from 1st November 2011 to 1st November 2012. Each procedure was assessed for costs, Country of treatment and length of stay. The costs included hospital and doctor fees. Colonoscopies with any intervention other than simple biopsy were excluded. Colonoscopies done in conjunction with any surgery, or that involved admission for complications, were excluded. Results: Overall, we assessed 260 colonoscopies in 49 different countries. 246 met the study criteria. China, The United Arab Emirates, Brazil and the USA had the highest volumes of colonoscopies in the year. The most expensive countries were The United States and Switzerland, with the average colonoscopy there costing €4, 742 and €4, 728 respectively. The most expensive colonoscopy was performed in the USA and cost €9, 743. The least expensive countries for colonoscopy were Croatia and India with an average cost of €101, and €105 per procedure respectively. Conclusion: There is a vast difference in costs for the same procedure, depending on the region of the world that the procedure is performed. The most expensive region being nearly 47 times as expensive as the cheapest region. We must ask ourselves what the difference in these costs relates to. What is it that Gastroenterologists in America and Switzerland are doing that equally qualified gastroenterologists in India are not?